Factors Defferentaiting the Fact and Type of Education Untertaken by People Aged 25+ in Poland - Szubert, Tomasz (Studia Oeconomica Posnaniensia, 2019)
Lifelong learning as a process of the continuous improvement and devel-opment of general and specific qualifications should be now a common life strategy of every human being. The economy and labour market are constantly changing, so without proper training it is difficult to keep up with all the changes, especially technological ones. It turns out, however, that not all people are able to adapt to the new reality. In the course of the study, using the logistic regression model, attempts were made to find out from what factors it depends that some people willingly under-take various types of educational activities, and some end their education only after completing compulsory education. In order to find such factors, apart from a review of foreign literature, own statistical analyses were carried out in which a set of data about respondents participating in the national panel study "Social Diagnosis" was used. In the course of the analysis, it turned out that people who eagerly improve their skills are primarily those who are well-educated, active in life, both socially and professionally. In this way, the gap between educated people and the rest of society is growing, which at the same time indicates which groups of people should be well cared for by decision-makers of social and educational policy.